2022
DOI: 10.1186/s12909-022-03672-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of a telehealth obesity OSCE and reliable checklist for assessment of resident physicians: a pilot study

Abstract: Background Obesity is a major public health problem, yet residents undergo little formal training and assessment in obesity-related care. Given the recent growth of telehealth, physicians must further learn to apply these skills using a virtual platform. Therefore, we aimed to develop an objective structured clinical examination (OSCE) with reliable checklists to assess resident ability to take a patient-centered obesity-focused history that was feasible over telehealth based on published obesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(33 reference statements)
0
0
0
Order By: Relevance
“…A recent publication described the transition of the ACGME faculty development hub at Michigan State University College of Osteopathic Medicine Statewide Campus System (MSUCOM SCS) from a traditional in-person educational course to a virtual format using Zoom as highly effective and completely or mostly met all course learning objectives [13]. A short report on 26 residents revealed that the virtual format was moderately reliable for assessing key obesity competencies among residents [14]. Educators agree that effective feedback procedures are fundamental to training and competency-based education.…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication described the transition of the ACGME faculty development hub at Michigan State University College of Osteopathic Medicine Statewide Campus System (MSUCOM SCS) from a traditional in-person educational course to a virtual format using Zoom as highly effective and completely or mostly met all course learning objectives [13]. A short report on 26 residents revealed that the virtual format was moderately reliable for assessing key obesity competencies among residents [14]. Educators agree that effective feedback procedures are fundamental to training and competency-based education.…”
Section: Discussionmentioning
confidence: 99%